(untitled) (TAMADDUN NURI JURNALI, 2026)
This article discusses proverbs, a special type of folk oral art, and their linguistic interpretation. It should be noted that in the study of proverbs, paying attention to their national-cultural characteristics, paying attention to their forms of expression in the culture of our people, allows us to reveal the linguistic and cultural aspects inherent in proverbs.